TRANSFORMATION OF AUDIT PROCEDURES IN A CONTEXT OF DECENTRALIZATION (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The research has an applied character. For the achievement of its aim scientific (abstraction, analysis, synthesis, induction, deduction) and specialized (bibliographic analysis, systemic analysis, economic and legal analysis, generalization and grouping and others like that) methodical approaches were used.It is concluded that decentralization is accompanied by a redistribution of plenary powers between the subjects of management, necessary for the implementation of their resources as well as responsibility. It is substantiated that the processes of decentralization can result in the redistribution of plenary powers between state and independent auditors as a result of changes in expectations of initiators of audit and users of its results. Direct and mediated influence of decentralization on the elements of audit as tasks from a grant to the confidence to the users of its results is identified.The results of the research, independently conducted by the author, expounded in the article are characterized of scientific novelty. In particular, influence of processes of decentralization on functioning of state and independent audit is first identified. The received results will facilitate the optimization of the use of information by economic entities on the basis of providing of high level of credibility to it from the side of users taking into account the confidence given on results of an audit.
Keywords: information, audit, decentralization, state audit, public control, management system.